2014
DOI: 10.1007/s11099-014-0019-8
|View full text |Cite|
|
Sign up to set email alerts
|

Accumulation of photosynthetic pigments in Larix decidua Mill. and Picea abies (L.) Karst. cotyledons treated with 5-aminolevulinic acid under different irradiation

Abstract: European larch (Larix decidua Mill.) and Norway spruce [Picea abies (L.) Karst.] synthesize chlorophyll (Chl) in darkness. This paper compares Chl accumulation in 14-d-old dark-grown seedlings of L. decidua and P. abies after shortterm (24 h) feeding with 5-aminolevulinic acid (ALA). We used two ALA concentrations (1 and 10 mM) fed to cotyledons of both species in darkness and in continuous light. The dark-grown seedlings of L. decidua accumulated Chl only in trace amounts and the seedlings remained etiolated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…High concentration of ALA (10-20 mM) also had negative effects on Chl accumulation in etiolated leaves of gymnosperms, such as Larix decidua Mill. and Picea abies (L.) Karst, after illumination (Pavlovič et al 2009, Maximová andSlováková 2014). These results suggested that exogenous ALA acted as a growth regulator on Chl content in plants at low concentrations (Hotta et al 1997, Liu et al 2011.…”
Section: Discussionmentioning
confidence: 95%
“…High concentration of ALA (10-20 mM) also had negative effects on Chl accumulation in etiolated leaves of gymnosperms, such as Larix decidua Mill. and Picea abies (L.) Karst, after illumination (Pavlovič et al 2009, Maximová andSlováková 2014). These results suggested that exogenous ALA acted as a growth regulator on Chl content in plants at low concentrations (Hotta et al 1997, Liu et al 2011.…”
Section: Discussionmentioning
confidence: 95%